Administrative and Legal Support in the Field of Housing Stock Restoration (Bulletin of Kharkiv National University of Internal Affairs, 2025)
This article is devoted to the analysis of administrative and legal support in the field of housing stock restoration. The research methodology is based on a system of philosophical, general scientific and special methods, in particular dialectical and formal-legal methods, as well as methods of analysis and synthesis.Administrative and legal support for the restoration of the housing stock is defined as a comprehensive system of organisational and managerial measures and regulatory and legal regulation for the implementation of mechanisms for the restoration of the housing stock (reconstruction, repair and renovation). It is substantiated that the organisational and managerial element of support includes the establishment of clear procedures for coordinating the actions of state authorities and local self-government bodies, defining the responsibilities and powers of participants in housing programmes, planning and implementing specific housing reconstruction projects, as well as ensuring interaction between public authorities, international organisations, construction contractors and the public. It is emphasised that the administrative and legal support for the restoration of the housing stock is aimed at optimising construction and reconstruction processes, simplifying the processing of permits and strengthening control over the effective use of financial resources, including international assistance.The practical significance of the research results lies in the possibility of using them in the development of a strategy for the restoration of the housing stock at the level of public administration programmes. It has been concluded that administrative and legal support in this area is a complex, coordinated system of management and regulatory and legal regulation of housing stock restoration. Promising areas for scientific research have been identified, in particular the study of administrative and legal support for control and monitoring of the implementation of housing stock restoration programmes.